METODE PEMBELAJARAN YANG DITERAPKAN RASULULLAH DALAM MENDIDIK SAHABATNYA - Sopiatun Nahwiyah; lyas Husti; Nurhadi (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research aims to find out what methods were used by Rasulullah SAW in educating his friends. The research method used is a qualitative descriptive method with a thematic method on hadiths related to the learning methods applied by the Prophet in educating his friends. The research findings showed that the learning methods that Rasulullah SAW applied in educating his friends were as follows: exemplary method, gradual delivery method, dialogue and question and answer method, Targhib and Tarhib method, advice method, lecture method, demonstration method, parable method, repetition method and story method. The methods applied by the Prophet were very effective and worthy of emulation in today's learning process.